Folate-conjugated dually responsive micelles for targeted anticancer drug delivery. Issue 42 (12th April 2016) - Zhao, Lingling; Zhang, Yajuan; Shao, Jia; Liang, Hongze; Na, Haining; Zhu, Jin
Abstract : Folate-conjugated dual-responsive micelles were developed, sustained and sensitive drug release from the drug loaded micelles was observed. Folate-targeted micelles showed higher anticancer activity and enhanced cellar uptake than non-targeted ones. Abstract : Phenylboronic acid and folate grafted chitosan hydrochloride (FHCSPBA) was synthesized and confirmed by FTIR and 1 H NMR. Glucose and pH dually responsive micelles were obtained through self-assembly of the amphiphilic polymers. The prepared FHCSPBA micelles displayed good biocompatibility and sustained drug release of the model drug doxorubicin hydrochloride (DOX). The cumulative drug release from the polymeric micelles showed obvious pH and glucose dependence and was accelerated by slightly decreasing the medium pH or increasing the glucose concentration. In vitro antitumor efficiency was evaluated by incubating the DOX loaded micelles with 4T1 breast cancer cells, and the results showed that folate-targeted micelles had higher antitumor activity than the non-targeted ones. Cellular uptake demonstrated by confocal microscopy indicated that free DOX was internalized in the nuclei of 4T1 cells, while the DOX loaded micelles were internalized in the cytoplasm. The cellular uptake of the micelles was enhanced by folate, with stronger fluorescence intensity in the cytoplasm, due to active FR-mediated endocytosis. These folate-conjugated glucose and pH dually responsive micelles may be a potential antitumor drug delivery system for cancer chemotherapy.